Peran Ekstrakurikuler Qira’at Dalam Pembentukan Kepribadian Pada Siswa Sekolah Dasar - Ismairoh, Bahrul; Sari, Devit Etika; Rahmania, Nurani (IERA, Islamic Education and Research Academy, 2020)
Extracurricular activities are fundamental undertakings within the school realm aimed at unearthing and motivating students in specific fields. The backdrop of this issue pertains to the implementation of the qira'at extracurricular program, aiming to shape students' personalities. The research questions are centered on the implementation of qira'at extracurricular activities at MI Islamiyah Jatipunggur, the role of qira'at extracurricular activities in shaping student personalities at MI Islamiyah Jatipunggur, and the challenges and solutions related to qira'at extracurricular activities at MI Islamiyah Jatipunggur. The study aims to comprehend the execution of qira'at extracurricular activities in forming the character of upper-grade students at MI Islamiyah. The research delves into the definitions of extracurricular activities, their implementation, and the essence of qira'at. To achieve these objectives, a descriptive qualitative research approach is employed, utilizing techniques such as observation, interviews, and documentation. Data sources encompass both primary and secondary sources. The data analysis technique is exploratory descriptive, aiming to depict the situation or phenomenon. The findings conclude that the role of qira'at extracurricular activities in shaping the personalities of upper-grade students at MI Islamiyah Jatipunggur aims to cultivate intelligent, skilled, and religiously disciplined students who apply the values of the Qur'an in their daily lives. The benefits include accommodating diverse student intelligences and conducting engaging and enjoyable education.